Results of Limousin breed in 2018 - Szűcs, Márton; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
The aim of this study was to give information to Hungarian breeders on characteristics of Limousin breed in 2018. This breeders' association was establish in 1989 by 10 persons and 10 companies. The increasing trend of the cattle number was observed in association of breeders between 2008 and 2018 years. Changing of membership was also positive in this period. The rate of the registrated herd it seems to be good: 67 % (12.999 animals). In the purebred registrated herds the number of cows (6.702 animals), and heifers (2.481 animals). were dominant. Very good easy calvings were observed in purebred (94%) and crossbred (97%) herds too. The weaning weigths adjusted to 205th day of calves by sex were respectively: bulls (262 kg) and heifers (228 kg). The following characteristics of cows were also very important for breeders: total type score (77 scores), age at first calving (33 months) and calving interval 418 days). Accordig to precedant information a good perspective can be concluded on Limousin breed in Hungary.
Keywords: Limousin cow; good conformation; easy calving; weaning weight